Keefektifan Pendekatan Realistic Mathematics Education (RME) Terhadap Pemahaman Konsep Matematika Siswa Pada Materi Sifat-Sifat Bangun Ruang - Sumarni, Sumarni; Makki, Muhammad; Wahyuningsih, Baiq Yuni (Lembaga Bale Literasi, 2025)
Conceptual understanding is one of the important abilities that students must have in learning mathematics. To achieve this ability, an appropriate learning strategy is needed, one of which is through the Realistic Mathematics Education (RME) approach. This study aims to test the effectiveness of the Realistic Mathematics Education (RME) approach on the mathematical concept understanding ability of fifth-grade students of SDN 37 Ampenan on the material of the properties of geometric shapes. This study uses a quantitative approach with a quasi-experimental type and the design used is Non-equivalent Control Group Design. The research sample consisted of 44 fifth-grade students divided into experimental and control classes. Data collection techniques were carried out with conceptual understanding tests and observation sheets for the implementation of learning. The data obtained were analyzed using the swimmer test (normality and homogeneity), followed by the hypothesis test of the Independent Sample T-test. The results of the study showed a significance value of 0.00